Human UDP-Glucuronosyltransferase 2B4 and 2B7 Are Responsible for Naftopidil Glucuronidation in Vitro - Liu, Xia-Wen; Rong, Yi; Zhang, Xing-Fei; Huang, Jun-Jun; Cai, Yi; Huang, Bi-Yun; Zhu, Liu; Wu, Bo; Hou, Ning; Luo, Cheng-Feng (Frontiers in Pharmacology, 2018)
Naftopidil (NAF) is widely used for the treatment of benign prostatic hyperplasia and prevention of prostate cancer in elderly men. These patients receive a combination of drugs, which involves high risk for drug-drug interaction. Naftopidil exhibits superior efficacy but must be administered at a much higher dosage than other therapeutic drugs. We previously showed that extensive glucuronidation of naftopidil enantiomers caused poor bioavailability. However, the metabolic pathway and mechanism of action of naftopidil enantiomer remain to be elucidated. The present study was performed to identify the human UGTs responsible for the glucuronidation of NAF enantiomers and to investigate the potential inhibition of UGT activity by NAF. The major metabolic sites examined were liver and kidney, which were compared with intestine. Screening of 12 recombinant UGTs showed that UGT2B7 primarily contributed to the metabolism of both enantiomers. Moreover, enzyme kinetics for R(+)-NAF, UGT2B7 (mean Km, 21 μM; mean Vmax, 1043 pmol/min/mg) showed significantly higher activity than observed for UGT2B4 and UGT1A9. UGT2B4 (mean Km, 55 μM; mean Vmax, 1976 pmol/min/mg) and UGT2B7 (mean Km, 38 μM; mean Vmax, 1331 pmol/min/mg) showed significantly higher catalysis of glucuronidation of S(-)-NAF than UGT1A9. In human liver microsomes, R(+)-NAF and S(-)-NAF also inhibited UGT1A9: mean Ki values for R(+)-NAF and S(-)-NAF were 10.0 μM and 11.5 μM, respectively. These data indicate that UGT2B7 was the principal enzyme mediating glucuronidation of R(+)-NAF and S(-)-NAF. UGT2B4 plays the key role in the stereoselective metabolism of NAF enantiomers. R(+)-NAF and S(-)-NAF may inhibit UGT1A9. Understanding the metabolism of NAF enantiomers, especially their interactions with metabolic enzymes, will help to elucidate potential drug-drug interactions and to optimize the administration of this medicine.